Tre Indlaeg om "Interlanguage Pragmatics" (Three Critiques of "Interlanguage Pragmatics"). ROLIG Papir No. 55 Bent Preisler, Ed. - Preisler, Bent (Distributed by ERIC Clearinghouse, 1996)
The three papers presented here are critiques to a Doctoral Dissertation defense titled "Interlanguage Pragmatics: Requests, Complaints, and Apologies." The responses are written by the "disputants" or members of the candidate's dissertation review committee. The first paper, "Den empiriske undersogelse i 'Interlanguage Pragmatics'" (The Empirical Examination in "Interlanguage Pragmatics"), by Bent Preisler, evaluates the dissertation's empirical examination of the topic. The second paper, "Sprogindlaering i teori og praksis i 'Interlanguage Pragmatics'" (Language Acquisition in Theory and Practice in "Interlanguage Pragmatics"), by Jacob Mey, focuses on the treatment of pragmatic theory, and the third paper, "Psykolingvistik, fremmedsprogspaedagogik og undervisningspraksis i'Interlanguage Pragmatics'" (Psycholinguistic, Foreign Language Pedagogical, and Instructional Practice in "Interlanguage Pragmatics"), by Torben Vestergaard, discusses the dissertation's review of foreign language pedagogical aspects. (VL)